The effect of externalities on adoption of social customer relationship management (SCRM) - Vicky Ching Gu; Jonathan Davis; Ray Qing Cao; John Vogt (International Journal of Quality Innovation, 2017)
The rise of social media technology has led to new customer relationship management tools that engage customers more easily and directly (social customer relationship management, SCRM). However, the usefulness of SCRM is contingent upon a successful adoption by an organization. Various technology adoption theoretical frameworks have been proposed for social media technologies generally, and for SCRM specifically. This paper extends the literature by exploring network externalities as a potential driver of SCRM adoption in organizations by surveying 363 supply chain professionals regarding their behaviors and uses of SCRM. The results suggest that network externalities have a substantial effect on adoption of SCRM in business organizations and that a perception of higher network externalities has a positive effect on adoption. This implies that organizations should select SCRM systems with better network externalities and also that they should educate their workforce about those strong network externalities leading up to the adoption.
Keywords: 650; Social CRM; CRM; Technology adoption; Supply chain management